Dose‐dependent study of effects of 532‐nm continuous wave laser on rat skin: A mechanistic insight. Issue 10 (20th June 2019) - Bora, Kiran; Kumar, Bhuvnesh; Prakash, Satya; Rathi, Ajay
Abstract: Visible lasers emitting in the green spectral region are being routinely employed in various medical and defense fields namely treatment of pigmented lesions, tattoo inks, port wine stains, dazzling the target or mob dispersal. Despite their increasing applications, lasers also tend to pose occupational hazards to operators, ancillary personnel, individuals undergoing laser therapies. This study was aimed at investigating the effects of different doses of 532‐nm continuous wave laser on rat skin. The present study demonstrated that higher fluences of 532‐nm continuous wave (CW) laser induces significant tissue damage through induction of tumor necrosis factor‐α, cyclooxygenase‐2, tumor protein (p53), PARP 1, caspase3 which in turn leads to tissue damage and cell death. Furthermore, level of heat shock proteins, pAkt were found up‐regulated as a cope up response to laser‐induced stress. On the basis of the findings, irradiation with 532‐nm CW laser up to 2.5 J/cm 2 was found within the safe exposure limits. Thus, it is probably the first attempt to demonstrate the tissue damage induced by 532‐nm CW laser on skin, which may help in choosing safe laser dose for certain skin‐based applications and evolving methods to ameliorate laser‐inflicted injuries. Abstract : Despite increasing implementation, lasers tend to pose occupational hazards to operators. The present study has demonstrated induction of significant tissue damage through up‐regulation of heat shock proteins, tumor necrosis factor ‐α, cyclooxygenase‐2 (COX‐2), tumor protein (p53), PARP 1, calpain small subunit 1 (CAPNS 1), caspase3 at higher fluences of 532‐nm continuous wave (CW) laser, leading to cell death and tissue disruption which was further confirmed by histopathological analysis. Based on the current study, irradiation with 532‐nm CW laser up to 2.5 J/cm 2 was found within the safe exposure limits.